Iowa Ornithologists' Union, Quarterly field report, fall 1995 - Kent, Thomas H. (Thomas Hugh), 1934-et al; Iowa Ornithologists' Unionet al (1995)
Quarterly field report for the fall of 1995 compiled by Thomas H. Kent. Epson - sheet feed/flatbed